1985
DOI: 10.1002/bit.260271106
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous denaturation of enzymes: A distributed activation energy model with nonuniform activities

Abstract: A model is proposed for the denaturation of enzymes based on heterogeneous enzyme subpopulations with nonuniform initial activities and nonzero final activities. The more frequently used simple first-order deactivation model is a special case of the model corresponding to the standard deviation of Gaussian distribution of activation energies approaching zero. Parametric studies made with the model are capable of simulating the reported trends in experimental data on the thermal profile and activity time behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…(1) and (3)] contains three kinetics constants; thus, shear must directly or indirectly affect k l , k-1, or k3. The second slope of the DS biphasic inactivation would be controlled by the coagulation reaction.25 Because the second slope of the curves (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(1) and (3)] contains three kinetics constants; thus, shear must directly or indirectly affect k l , k-1, or k3. The second slope of the DS biphasic inactivation would be controlled by the coagulation reaction.25 Because the second slope of the curves (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The activity versus deactivation-time data presented in ref. 23 were correlated by means of the equation: aft) = (a, -a,)e-" + a, (1) This suggested that the following deactivation path occurs: N -X (9 A straightforward transition from native enzyme to a final, still-active configuration takes place obeying irreversible, first order kinetics. In previous works on the deactivation kinetics of enzymes operating in aqueous solution,6 a series mechanism was taken into account:…”
Section: Introductionmentioning
confidence: 99%
“…It should be emphasized that regression is strongly influenced by data at f > 25 h, not reported in the graph, that confirm the actual existence of an asymptote. The interpolating curve (solid line) reported in Figure 1 corresponds to the correlating equation:It should be noted that the model contains the same number of regression parameters (three) as Eq (1)…”
mentioning
confidence: 99%
“…2a illustrates the aggregation of the latter). The reaction involving the aggregation of the dimer would take on the form P2 + P: p;+2 (7) where P: is an aggregated species. The resulting aggregate can be stabilized by several types of molecular interactions.…”
Section: Mechanisms Of Irreversible Inactivationmentioning
confidence: 99%